Yin-Yang Staining Technique to Create a Nonstained Internal Limiting Membrane Flap to Cover Large Idiopathic Macular Holes - Ni, Yao; Xing, Shuwen; Chen, Baizhou; Zhang, Zhaotian (Journal of vitreoretinal diseases (Print), 2025)
To describe a modified technique for negative and positive (Yin-Yang) staining of the internal limiting membrane (ILM) to create a nonstained ILM flap that covers large idiopathic macular holes (MHs). Consecutive patients with large idiopathic MHs (>400 μm) were prospectively included in the study. After the central vitreous was removed, a droplet of triamcinolone acetonide was injected, covering the MH and surrounding area. Subsequently, indocyanine green (ICG) was injected to stain the outer area of the ILM, followed by creation of a flap from the temporal stained area. Finally, the nonstained ILM flap was inverted to cover the MH. The main outcomes included the best-corrected visual acuity (BCVA), macular contour, and integrity of the outer retina. This study comprised 31 patients (31 eyes). Of the eyes, 28 (90.3%) achieved primary MH closure. The mean minimum linear diameter and base diameter of the MH was 593 ± 119 μm and 1082 ± 242 μm, respectively. At the 6-month follow-up, 12 eyes (38.7%) and 9 eyes (29.0%) had regained a U-shaped or V-shaped macular contour, respectively. In addition, the mean logMAR BCVA improved from 1.06 ± 0.30 preoperatively to 0.56 ± 0.31 ( < .001). Twenty-one eyes (67.7%) and 16 eyes (51.6%) had regained integrity of the external limiting membrane and ellipsoid zone, respectively, at the 6-month follow-up. The modified ILM staining technique using triamcinolone acetonide and ICG sequentially is a safe and effective method of creating a nonstained ILM flap that covers large MHs and prevents the foveal area from coming into direct contact with ICG.